Tingkat Kesadaran Kurangnya Pemahaman Masyarakat Tentang Daur Ulang Limbah Sampah Plastik Masyarakat TPS - Romauli situmorang; Habibatul Qolbi Sumardi; Kurnia Simbolon; Mira Susila Warni; Meilinda Suriani Harefa (Fakultas Teknik Universitas Cenderawasih, 2023)
This research uses a qualitative approach with a case study method to explore in-depth understanding of the role and impact of plastic waste recyclers in the context of environmental conservation and natural resource utilization. Narrative data in the form of written or spoken words from people, attitudes, and objects that can be observed are collected through the Documentation and Observation approach. The research location involved three places, namely TPS Jl. Ambil No. 83 Sidorejo Hilir Village, Medan Tembung Sub-district, TPA Air Terjun in Medan Marelan Bandar Selamat Village, and Bank Sampah Karya Mitra Jl. Datuk Kabu, Bandar Klippa, Percut Sei Tuan Sub-district, Deli Serdang Regency. The focus of observation is the position of the Waste Disposal Sites (TPS) in Medan Tembung Sub-district, Percut Sei Tuan Sub-district, and Bandar Selamat Landfill. Qualitative data analysis techniques were conducted by studying the answers collected from the research subjects, with the aim of analyzing the effectiveness, constraints, and potential in the practice of plastic waste recycling. Plastic waste is identified as a significant source of environmental pollution, and this research tries to investigate the contribution of recycling as a critical solution to reduce its negative impact.